Aprendizagem empreendedora em contexto de insucesso empresarial: estudo com empreendedores de micro e pequenas empresas - Dias, Tania Regina Frota Vasconcellos (2015)
The role that knowledge acquired from failure can play in business environment, in recent years, has shown a relevant interest in entrepreneurship. In this scenario, this study aims to analyze how business failure provides entrepreneurial knowledge for entrepreneurs of micro and small enterprises in creating new business. Therefore, we proceeded to the integration of two conceptual research models from the insertion of Cope's learning journey (2011) in the bulge of the framing outlined by Politis (2005) on entrepreneurial learning. We described the entrepreneurial career experiences until business interruption, as well as the learning journeys. Apart from that, we analyzed the learning dimensions of business failure addressing the transformation of career experience into entrepreneurial knowledge. We adopted a qualitative research design with an in depth exploratory approach (Mason, 1996), which is characterized by a longitudinal cross-sectional view. Eight entrepreneurs were selected by convenience and availability. We used snowball methodological technique and the contacts were established by appointment with several entrepreneurs in the study area. For gathering data, it was decided to use interviews based on script and they were applied between May 2013 and October 2014. The interviews were recorded, transcribed, classified, coded and analyzed. We used the thematic content analysis taking narrative as basis. Given the evolution of entrepreneurial learning process and the consequent acquisition of knowledge through lived experiences, the research found out that all entrepreneurs, in the time they faced the failure of their business, showed a spontaneous and instant reflexive action, because they did not fall inert in face of the reasons that led them to slow down and close their activities. Thus, we infer that this knowledge is suitable to increase the ability of understanding and interpreting new events and circumstances, and thus, overcoming the adversities and obstacles concerning entrepreneurial activity, enable entrepreneurs to open a new business. Finally, we present theoretical and practical contributions of this study, as well as the research limitations and suggestions for further researches.